2015
DOI: 10.1073/pnas.1599993112
|View full text |Cite
|
Sign up to set email alerts
|

Grandmothering life histories and human pair bonding

Abstract: The evolution of distinctively human life history and social organization is generally attributed to paternal provisioning based on pair bonds. Here we develop an alternative argument that connects the evolution of human pair bonds to the male-biased mating sex ratios that accompanied the evolution of human life history. We simulate an agent-based model of the grandmother hypothesis, compare simulated sex ratios to data on great apes and human hunter-gatherers, and note associations between a preponderance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 89 publications
5
48
0
Order By: Relevance
“…These factors include low variance in men's mate value (71,72), higher percent contribution by men to household diet (73), dilution of wealth transmission across generations (74), and a male-biased operational sex ratio (75,76). In populations where operational sex ratios are male biased, men may derive more value from status as a means of maintaining an existing mate than as a means of acquiring new mates (75), or at least more so than in populations where operational sex ratios are female biased. In the latter, men suffer fewer costs from pursuing a lesscommitted sexual strategy because men are in greater demand (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors include low variance in men's mate value (71,72), higher percent contribution by men to household diet (73), dilution of wealth transmission across generations (74), and a male-biased operational sex ratio (75,76). In populations where operational sex ratios are male biased, men may derive more value from status as a means of maintaining an existing mate than as a means of acquiring new mates (75), or at least more so than in populations where operational sex ratios are female biased. In the latter, men suffer fewer costs from pursuing a lesscommitted sexual strategy because men are in greater demand (76).…”
Section: Discussionmentioning
confidence: 99%
“…2). This reduction in reproductive payoffs to high status could reflect increased interdependence in food production, greater ability to form leveling coalitions, increased payoffs to mateguarding due to changes in sex ratio, or increased opportunities for female choice (75,78). Arranged marriage has likely been common since at least the early migrations of humans out of Africa (79), but even when male kin control marriage arrangements, females may exert significant mate choice via surreptitious extrapair copulation (80).…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of these typically bird-like male-biased sex ratios to human evolution is currently an open question. However, while our closest relatives have typical mammalian female-biased sex ratios51, human sex ratios are considerably more male-biased83652 and bird-like4953. Thus the question becomes, did our ancestors experience a change in the direction of the sex ratio bias, resulting in a shortage of women?…”
Section: Discussionmentioning
confidence: 99%
“…Those "hard" lines of evidence-stone tools with cut-marked bones of large animals and increased cranial capacity in genus Homo-have long made meat eating and brain size favored candidates to explain the evolution of our longevity (14). Schwarz et al's demonstration (1) shows that genomics offers a line of evidence into the character and timing of life history shifts that might themselves have been the crucial foundation for many distinctively human features (15,16). Although the authors found the derived CD33 allele only in modern humans, the small number of Neanderthal and Denisovan genomes currently available cannot rule out similar polymorphisms in those taxa.…”
Section: How Old Is Human Longevity?mentioning
confidence: 99%